Performance and Genetic Variability of Okra (Abelmoschus esculentus (L.) Moench) Genotypes in Ethiopia for Agromorphology and Biochemical Traits. (27th January 2022) - Mohammed, Jemal; Mohammed, Wassu; Shiferaw, Eleni
Abstract : No research has been done to assess the genetic diversity of Okra ( Abelmoschus esculentus ) genotypes in Ethiopia based on the combination of agromorphology and biochemical traits of the crop. Such an assessment would assist in the development of high fruit yield and nutritionally good cultivars. Therefore, 36 okra genotypes were evaluated for 29 agromorphological and biochemical traits at the Melkassa Agricultural Research Center (Ethiopia) during the 2018 main rainy season, using a 6 × 6 simple lattice design. Analysis of variance showed significant differences among genotypes for all the studied traits, except number of flower epicalyxes and fruit diameter. Genotypic coefficients of variation and phenotypic coefficient of variation were high for number of branches, internode length, fresh fruit weight, number of mature pods, fruit yield per plant, fruit yield per hectare, seed yield per plant, seed yield per hectare, and seed protein content. Heritability values ranged between 33.63 and 99.81%, while the genetic advance as percentage of mean ranged between 4.29 and 95.45%. High broad sense heritability was coupled with high GAM for plant height, branch, internod length, fruit length, panicle length, fresh fruit weight, number of fruits per plant, number of mature pods, seed yield per plant, seed yield per hectare, and fibre and protein content. In conclusion, this study showed the presence of genetic variation among genotypes for fruit yield, seed yield, and nutritional content, indicating the potential success of developing okra varieties for high fruit yielding and good nutritional content.